(untitled) (World Economics and Finance Bulletin, 2025)
This paper analyzes the roles of key actors involved in investment processes within industrial enterprises in Uzbekistan. Using statistical data from 2020 to 2024, a multiple linear regression model was applied to assess the influence of government investment, private capital, commercial bank loans, and foreign direct investment on the total investment volume. The results demonstrate that commercial bank loans and public investments are the most significant drivers, while private and foreign investments also contribute meaningfully. The study highlights the importance of a multi-actor investment strategy and recommends targeted policy interventions to enhance the efficiency of industrial investments.